Pengaruh Keterampilan Manajerial Kepala Sekolah dan Status Sosial Ekonomi Guru terhadap Kinerja Guru SMA Negeri I Merauke–Papua - Basilius Redan Werang (Jurnal Aplikasi Manajemen, 2012)
Teacher’s performance is identified as one of the important factors in achieving the objectives of national education. Two factors that theoretically affect the teacher’s performance are principal managerial skills and teacher’s social-economic status. This study is aimed to describe the tendency of principal managerial skills, teacher’s social-economic status and teacher’s performance; and to verify partial and simultaneous relationships among the factors. Samples that consist of 56 teachers were drawn by applying a systematic proportional random sampling technique from the population that consists of 60 teachers at first State Senior High School in Merauke city. Based on descriptive analysis, results of this study show that all variables are categorized as high category. Meanwhile, based on regression analysis with respect to degree of truth 95 % and of fault 5 %, and based on the hypotheses as well, conclusions drown as the findings of this study are as follows: (1) there is a significant influence between principal managerial skills and teacher’s performance at first State Senior High School in Merauke city; (2) there is a significant influence between teacher’s social-economic status and teacher’s performance at first State Senior High School in Merauke city; and (3) there is a simultaneous significant influence between principal managerial skills and teacher’s social-economic status with teacher’s performance at first State Senior High School in Merauke city.Keywords: principal managerial skills, teacher’s social-economic status, teacher’s performance